Rational inattention in hiring decisions - Sushant Acharya; Shu Lin Wee (Federal Reserve Bank of New York, 2019)
We provide an information-based theory of matching efficiency fluctuations. Rationally inattentive firms have limited capacity to process information and cannot perfectly identify suitable applicants. During recessions, higher losses from hiring unsuitable workers cause firms to be more selective in hiring. When firms cannot obtain sufficient information about applicants, they err on the side of caution and accept fewer applicants to minimize losses from hiring unsuitable workers. Pro-cyclical acceptance rates drive a wedge between meeting and hiring rates, explaining fluctuations in matching efficiency. Quantitatively, our model replicates the joint behavior of unemployment rates and matching efficiency observed since the Great Recession.
Keywords: D8; E32; J63; J64; 330; rational inattention; hiring behavior; matching efficiency; composition of unemployed